Bibliometric Analysis of Coral Reef Conservation and Mooring Buoy Applications in Sustainable Marine Tourism - Erdina Arianti; Wibowo Harso Nugroho; R. Kusnindar Priohutomo; Moh. Muria Armansyah Sugiarto; Arief Syarifuddin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Ship mooring at coral reef slope is a high risk for Indonesian coral reefs, particularly in tourist based coastal environment. Mooring buoy technology is a well-established component of offshore engineering but has not yet been fully adapted to shallow coral reef ecosystems. This bibliometric analysis of 2015-2024 publications was performed using Lens.org and VOSviewer in search of research trends and knowledge gaps. The study finds six main research clusters, including: environmental management, tourism, and technical aspects; conservation, ecosystem behaviour, and protected areas; sustainable development and threats; coral reefs and ecosystem resilience; fisheries and the deep sea; and sea monitoring and conditions. While coral reef conservation research also has good representation, the following are important gaps identified in this study: mooring technology is very isolated in its own network with little apparent influence on conservation or oceanographic fields. This reflects two major gaps: mooring technology are not associated with conservation objectives, and mooring designs have not been adapted to Indonesia’s unique oceanographic conditions. This research demonstrates that developing mooring buoys suitable for Indonesian shallow waters represents a strategic opportunity to bridge engineering with practical conservation. Future research should focus on three areas: site-specific hydrodynamic characterization at marine tourism destinations; numerical simulation of adaptive mooring designs; and community-based implementation frameworks for long term sustainability.